A Case of Granulomatosis with Polyangiitis Causing Hydroureter and Hydronephrosis - Farzin Farpour; Adriana Abrudescu (Case Reports in Rheumatology)
Granulomatosis with Polyangiitis (GPA, formerly known as Wegener) is a systemic vasculitis characterized by granulomatous involving upper and lower respiratory tract and can also cause necrotizing glomerulonephritis (Umemoto et al. 2012 and Takala et al. 2011). GPA is associated with antineutrophil cytoplasmic autoantibodies (ANCA) against serine proteinase 3 (PR3) (Takala et al. 2011, Dufour et al. 2012, and Berthoux et al. 2011). This disease usually starts with involvement of the upper and lower respiratory tracts and also can involve kidney, eyes, skin, central and peripheral nervous systems, and gastrointestinal tract (Umemoto et al. 2012, Takala et al. 2011, and Berthoux et al. 2011). We describe a case of GPA that presented with abdominal pain. Computed tomography (CT) scan with contrast showed right sided moderate hydronephrosis and hydroureter, to the level of the right common iliac artery. There was also mural segmental thickening in common iliac artery which was thought to be the cause of the ureteral obstruction and hydronephrosis. Our case shows that mural segmental thickening in common iliac artery happened due to GPA and caused hydronephrosis. In addition, most of the cases with hydronephrosis due to GPA went through urology intervention such as stent placement but in our case hydronephrosis resolved with medical management.